Prediction and design of protein structures and interactions - Baker, David (Henry Stewart Talks, 2007)
Modeling of macromolecular interactions, Conformational sampling, Docking low-resolution search, High resolution refinement, Docking protocol, Side chain flexibility and modeling, Ab initio structure prediction, Computational protein design, Simultaneous sequence-structure optimization, Protein interface design, Properties of free energy landscapes of macromolecules
Reviewed at 2015/07/16